Investigation of Electric Field Distribution Inside 500/220 kV Transformation Substations during Different Working Conditions - Sayed A. Ward; Samy M. Ghania; Essam M Shaalan (International Journal of Applied Power Engineering (IJAPE), 2014)
This study depicts the electric field distributions inside a typical 500/220 kV open distribution substation under actual loading conditions and during different working conditions, Hot-Stick position and Bar-Hand position. The electric field is investigated for different workers heights of 1m, 1.5m and 1.8m above ground during normal working condition (Hot-Stick position) inside this substation. This in addition to assessment of the electric field at a height levels of 8m, 11m, 14m and 17m above ground as positions for live line maintenance under 220 kV Busbars, 500 kV Busbars, 220 kV Incoming and Outgoing feeders and 500 kV Incoming and Outgoing feeders respectively. In this study the simulation results of the electric field obtained using three dimensional (3D) computer model for existing typical high voltage transformation substation are compared with field values measured inside this typical substation and presented and discussed not only in the form of contour maps but also in the form 3D surface and wireframe maps. The simulation results are good matched and agreed with measured values. This in addition to the electric field will be tabulated and compared to international guidelines for personnel exposure to electric field. This study will serve for planning service works or for inspection of equipment inside high voltage (HV) power transformation substations.